IPTEKS EFEKTIFITAS PENGENDALIAN INTERN ASET TETAP PADA BANK INDONESIA KANTOR PERWAKILAN SULAWESI UTARA - Fauziyyah, Wanda; Sondakh, Jullie J. (Universitas Sam Ratulangi, 2018)
Bank Indonesia Representative Office in North Sulawesi is a Bank Indonesia of Representative Office domiciled in North Sulawesi Province. As a central bank, BI has one main goal, namely achieving and maintaining the stability of the rupiah value. Seeing the complexity and task of BI, then the buildings and facilities in the Bank Indonesia Office Complex (KOPERBI) must be managed appropriately. Good facility management can improve performance and employee productivity and also can guarantee that existing facilities function properly. There is a need for operational procedures and guidelines effective and efficient that can assist in the implementation of internal controls. Good internal control is needed to secure fixed assets held in an entity to plan, establish, maintain or extend the useful life of fixed assets and improve operations to protect assets. Can be done using internal control to direct the company's operations, protect assets, and prevent abuse of the system that has been formed. Based on observations made on Bank Indonesia Representative Office in North Sulawesi Internal control is carried out effectively and efficiently, but there are some things that must be considered such as completeness of documents in planning activities, Procurement Activities, Maintenance Activities, and Removal Activities. Completeness of these documents aims to make it easier for interested parties in examining and assessing the facilities and infrastructure contained in Bank Indonesia Representative Office in North Sulawesi.